DUFOUR AND THE DESIMBOLIZATION OF MAN, THE BAKHTINIAN DIALOGICAL VOICE AS RESISTANCE - Silva Monteagudo, Barbara Cibelli da [UNESP] (Fundacao Univ Tocantins, 2021)
This text deals with the Bakhtinian dialogia as a possibility of resistance to desimbolition (DUFOUR, 2005), aims to conceptualize the desimbolization of man in postmodernity and to point out dialogism and literature as important processes in the school as a mechanism of human insertion in the generational thread that historically links one generation to another. He conceives the word as a social construction, rooted in valuation, social sign. It is part of research on children's literature and socialization circles as a process of appropriation of human culture. This study has a bibliographic character. Our thesis is that literature enables dialogue with the word, it constitutes a social statement and at the same time it reflects the society of an era it also refracts it, therefore it reflects culture at the same time that also transgresses it because it manages to capture what is still fermenting in society.
Keywords: Literature; Desimbolization; Dialogia; Resistance